Reduksi Kerusakan Fisik Mentimun dengan Jenis Kemasan yang Berbeda Setelah Simulasi Transportasi: Penelitian - Ni Wayan Arya Utari; Savitri Wahyuni; Setyadi Gumaran; Muh. Kusmali; Harmiansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Cucumber (Cucumis sativus L.) is one of the most popular fruit vegetables due to its various benefits. However, the transportation process can lead to mechanical damage such as bruising, scratching, and cracking. This study aims to evaluate the effect of different packaging types on the physical characteristics of cucumber (Cucumis sativus L.) and to assess the extent of mechanical and physical damage following simulated transportation and storage. Three types of packaging were used in this study: polyethylene plastic (PE), polyethylene plastic combined with corrugated cardboard (PEKG), and polyethylene plastic combined with plastic crates (PEKP). The transportation simulation was conducted for 1 hour. The results showed that the lowest mechanical damage occurred in PEKG packaging (5.5%) and the highest in PE (24.07%). The highest weight loss was recorded in PE (4.86%), while the lowest occurred in PEKG (4.17%). The lowest firmness value was observed in PE (20.10 N), and the highest in PEKG (20.42 N).